Cognitive failure susceptibility and personality: Self-directedness predicts everyday cognitive failure. (1st June 2020) - Markett, Sebastian; Reuter, Martin; Sindermann, Cornelia; Montag, Christian
Abstract: Susceptibility to everyday cognitive failure is often assessed in clinical and vocational settings to estimate the effectiveness of interventions or to predict performance and performance decline in stressful situations. Comparatively little is known about the relationship between cognitive failure susceptibility as quantified by the Cognitive Failure Questionnaire (CFQ) and personality factors. We examined the relationships between the CFQ and the seven personality dimensions as assessed by the Temperament and Character Inventory (TCI). Through regression analyses with out-of-sample prediction in two samples, we explained around 18% of the variance in cognitive failure from personality scores. We established the character trait self-directedness as the main inversely related predictor of everyday cognitive failure. High cognitive failure thus seems to reflect low levels of self-confidence, self-acceptance, and responsibility for one's own actions which are the key aspects of self-directedness. This result provides evidence for the previously stated 'complaint' hypothesis that cognitive failure results from a poor self-image rather than a vulnerability to stress.